INDONESIAN’S TOURIST SHOPPING JOURNEY (TSJ) DURING AND AFTER THE COVID-19 PANDEMIC - Rahayu, Siti (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2024)
This study aims to determine the effect of performance expectancy, effort expectancy, social influence, facilitating condition, pleasure, and arousal on the intention to use smartphones on the Tourist Shopping Journey (TSJ) on domestic tourists in Indonesia. There are two conditions in this study, namely during the Covid-19 pandemic and after. Data processing in this study used SPSS 24.0 and AMOS 24.0. The results showed that during the Covid-19 pandemic, the variables of facilitating condition and pleasure affected the intention to use smartphones when shopping on tourist trips. Meanwhile, in conditions after the Covid-19 pandemic, the influential variables are facilitating conditions and arousal.